2004
DOI: 10.1097/01.ju.0000143448.04161.cc
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Patients With Lymph Node Positive Prostate Cancer Following Radical Prostatectomy: Long-Term Results

Abstract: Local tumor bulk and the number/percent of involved lymph nodes significantly affect disease progression and the survival rate. Radical prostatectomy may offer long-term survival in patients who have limited tumor bulk and nodal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
192
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(206 citation statements)
references
References 17 publications
10
192
0
4
Order By: Relevance
“…Overall, clinical recurrence-free and BCR-free survival at 10 years was an impressive 74, 69, and 40%, respectively. 18 Other studies have demonstrated similar outcomes suggesting that PLND may remove all metastatic disease and allow good long-term progressionfree survival PFS in select cases. 19,20 Joslyn and Konety 21 demonstrated in a Surveillence Epidemiology and End Results database study that patients who underwent PLND with excision of at least 4 LN had improved CSS compared with patients who did not undergo PLND.…”
Section: Ongoing Controversies In Plndmentioning
confidence: 80%
See 1 more Smart Citation
“…Overall, clinical recurrence-free and BCR-free survival at 10 years was an impressive 74, 69, and 40%, respectively. 18 Other studies have demonstrated similar outcomes suggesting that PLND may remove all metastatic disease and allow good long-term progressionfree survival PFS in select cases. 19,20 Joslyn and Konety 21 demonstrated in a Surveillence Epidemiology and End Results database study that patients who underwent PLND with excision of at least 4 LN had improved CSS compared with patients who did not undergo PLND.…”
Section: Ongoing Controversies In Plndmentioning
confidence: 80%
“…Some advocate extending the dissection up to the ureteric crossing or beyond. 18 Larger templates have the advantage of including more of the potential landing sites for the metastatic disease at the cost of additional time to perform the procedure and increased morbidity. 24 Heidenreich et al performed an extended template PLND (ePLND) on 103 consecutive patients and compared this with 100 patients who underwent standard PLND.…”
Section: Anatomic Extent Of Lymph Node Dissectionmentioning
confidence: 99%
“…They also demonstrated that radical prostatectomy patients with a single nodal metastasis were at a threefold higher risk for systemic progression and fourfold higher risk for prostate cancer death, but in comparison, those with two or more lymph node metastases were twice as likely to experience systemic progression as well as prostate cancer death. Similarly, Skinner's group confirmed a 10-year recurrence-free survival rate following a radical prostatectomy of 70%-73% in patients with one or two lymph node metastases, but only a 49% rate in those with five or more involved nodes [63]. In addition, when pathological specimens were reviewed, Griebling et al [64] found that the 5-year overall survival rate for patients with extracapsular nodal extension was 55%, compared with 71% for those with histologically confined prostatic nodal metastases.…”
Section: Prostate Cancermentioning
confidence: 81%
“…In addition, a Ͻ15% density in patients conferred a 5-year PSA progression-free survival rate of 43% following an extended PLND, compared with only 10% after a limited PLND. Daneshmand et al [63] also identified that patients with a Յ20% lymph node density had a 72% 10-year recurrence-free survival rate, compared with a 47% 10-year survival rate for those with Ͼ20% density.…”
Section: Prostate Cancermentioning
confidence: 99%
“…This issue is controversial for prostate cancer management given the lack of prospective data and ambiguous retrospective studies 1 and is illustrated in the variation in our clinical practice guidelines (Table 1). [2][3][4][5] Coincident with the decrease of lymph node involvement (LNI) in most prostatectomy series 6,7 there has been remarkable decline in pelvic lymph node dissection (PLND) for low-risk disease, 8 although this trend may be less apparent in Canada. 9 A risk-adapted approach to PLND remains controversial; it has been suggested that other complicating elements are involved in its decline, including changes in surgical approach as well as reimbursement issues.…”
mentioning
confidence: 99%